Supporting Students' Self-Directed Learning in EFL Speaking Classroom by Using Cake Application - Indah Sri Redjeki; R. Muhajir (Journal of English Language Learning, 2022)
Students are currently on the verge of a technological revolution known as Industry 4.0. As a result, it is critical for today's educators to be able to integrate a teaching-learning method with educational technology as appropriate media in order to achieve the goal of effectively teaching and learning EFL speaking. Smartphones or mobile devices can be loaded with a variety of language-learning apps. One of them is the Cake application, which will serve as the focal point of this current study to supplement previous relevant research. Using a case study research design, 25 third-semester English education program students as the research participants were asked to explore Cake at home for a week while recording all of their activities and discoveries. They were then given open-ended questionnaires to express their perceptions with the app. The results demonstrated that the Cake supported students' self-directed learning in EFL speaking classroom since it was easy, simple, interesting to use, and contained a lot of features for English learning independently, so they could manage themselves to decide the learning goals of using the app and control the learning process. The app could also be used to help them improve some components of speaking skills (pronunciation, vocabulary and grammar) which are the most common issues they face when speaking English. As a result, this app could be a good way for EFL students to improve their speaking skills and support their self-directed learning.